PENGARUH METODE LATIHAN INTERVAL DAN KEMAMPUAN AGILITY TERHADAP PENINGKATAN KETERAMPILAN DRIBBLING PERMAINAN SEPAK BOLA - Mubarok, Mochamad Zakky (Jurnal Olahraga, 2016)
The objectives of this study are: (1) To find out the difference between intensive interval training methods and extensive interval methods to improve the basic skills of football dribbling; (2) To find out the interaction of the interval training method with the ability of agility to improve soccer dirbling skills; (3) To know the effect of the intensive interval training method with the extensive interval method on the group of high agility abilities on improving the basic skills of football dribbling; (4) To determine the effect of the intensive interval training method with the intensive interval method on the low agility ability on improving basic soccer dribbling skills. The method used in this study was an experiment with a 2 x 2 factorial design. The population was 46 people and a sample of 24 people in Propel Soccer School. The results showed that the intensive interval method was better than the extensive interval method described in hypothesis I (F = 5.554. P-value = 0.029 <0.050). There was no interaction with the interval training method with the ability of agility to improve football's dirbbling skills for hypothesis II (F = 0.906. P-value = 0.353> 0.050). The conclusions of the results of this study are: (1) The intensive interval training method has a better effect than the extensive interval method on improving the basic skills of football dribbling; (2) There is no interaction with the interval training method with the ability of agility to improve soccer dirbling skills; (3) The effect of the intensive interval training method is better than the extensive interval method in the group of high agility abilities on improving basic soccer dribbling skills; (4) The effect of the extensive interval training method is better than the intensive interval method on the low agility ability on improving the basic skills of football dribbling.